Men’s non-disclosure of intimate partner violence : a case study of Ga-Masemola, Sekhukhune District in Limpopo Province - Kgatle, Mankwana Othilia (My University, 2021)
Intimate partner violence among heterosexual couples seem to be on the rise with men as victims of female perpetrated violence. Recent research on this phenomenon indicates that partner violence against men is a social and health problem that is hidden and unspoken of in most societies. The current study was aimed at exploring men’s non-disclosure of intimate partner violence at Ga-Masemola, Sekhukhune District in Limpopo Province. Qualitative research methodology and exploratory research design were applied to successfully explore men’s non-disclosure of IPV. The target population of this study was heterosexual male victims of ages 18 and above. Non-probability sampling of blended convenience sampling and snowball sampling were employed. Data was collected using a semi-structured interview guide with open-ended questions and was analysed through thematic analysis of qualitative data. The results of the study have revealed that male victims of partner violence hide their situations. Determinants of non-disclosure were found to include men’s own personal feelings of fear to disclose, masculinity factors, societal expectations and cultural norms, which negatively affect men’s decisions to disclose. Help-seeking behaviour of male victims remains a huge challenge for most male victims. Due to fear of ridicule, disbelief and false accusations, abused men seem to lack courage to seek help. The shocking outcome is that most victims appear to lack knowledge of services available for them. The study recommends that public education, advocacy and appropriate gender-sensitive intervention programmes be implemented to overcome the effects of violence and to prevent further victimisation.
Thesis (M. A. (Social Work)) -- University of Limpopo, 2021
Keywords: Intimate partner violence; Male victims; Female perpetrators; Masculinity; Shame; Non-disclosure; Help-seeking; Intimate partner violence; Same-sex partner abuse; Heterosexuals